The use of real-time monitoring during flywheel resistance training programmes: how can we measure eccentric overload? A systematic review and meta-analysis - Muñoz-López, Alejandro; de Souza Fonseca, Fabiano; Ramírez-Campillo, Rodrigo; Gantois, Petrus; Javier Nuñez, Francisco; Y. Nakamura, Fabio (Biology of Sport, 2021)
This systematic review and meta-analysis aimed to analyse the technologies and main training variables used in the literature to monitor flywheel training devices in real time. In addition, as the main research question, we investigated how eccentric overload can be effectively monitored in relation to the training variable, flywheel shaft type device and the moment of inertia selected. The initial search resulted in 11,621 articles that were filtered to twenty-eight and seventeen articles that met the inclusion criteria for the systematic review and meta-analysis, respectively. The main technologies used included force sensors and rotary/linear encoders, mainly to monitor peak or mean force, power or speed. An eccentric overload was not always achieved using flywheel devices. The eccentric overload measurement wasrelated to the main outcome selected. While mean force (p = 0.011, ES = -0.84) and mean power (p < 0.001, ES = -0.30) favoured the concentric phase, peak power (p < 0.001, ES = 0.78) and peak speed (p < 0.001, ES = 0.37) favoured the eccentric phase. In addition, the lower moments of inertia (i.e., from 0.01 to 0.2 kg·m2 ) and a cylindrical shaft type (i.e., vs conical pulley) showed higher possibilities to achieve eccentric overload. A wide variety of technologies can be used to monitor flywheel devices, but to achieve eccentric overload, a flywheel cylindrical shaft type with low moments of inertia is advised to be used.